﻿Integrative taxonomy delimits and diagnoses cryptic arboreal species of the Cyrtodactylus brevipalmatus group (Squamata, Gekkonidae) with descriptions of four new species from Thailand - L. Lee Grismer; Anchalee Aowphol; Siriporn Yodthong; Natee Ampai; Korkhwan Termprayoon; Akrachai Aksornneam; Attapol Rujirawan (ZooKeys, 2022)
Species delimitation and species diagnosis must remain separate operations to avoid constructing taxonomies comprised of non-monophyletic species based on morphological similarity as opposed to phylogenetic propinquity. This is particularly true for highly specialized species such as the range-restricted upland taxa in the Cyrtodactylus brevipalmatus group of Indochina where strong selection pressure for an arboreal lifestyle has contributed to morphologically similar but distantly related species. This in turn, has resulted in a history of erroneous taxonomies that have actually obscured rather than revealed the diversity within this group. A Bayesian phylogeny of the C. brevipalmatus group recovered at least 15 putative species-level lineages, at least seven of which are undescribed, and of which four are described herein. A total evidence morphological data set comprised of 16 normalized morphometric, 15 meristic, and seven categorical characters scored across 51 individuals was subjected to a multiple factor analysis (MFA) and an analysis of variance (ANOVA) to diagnose the putative species. These new species descriptions contribute to focusing attention to the unrealized diversity in upland tropical ecosystems, which due to climate change, are some of the most impearled ecosystems on the planet. Thus, it is paramount that taxonomies do not conflate species identities and underrepresent true diversity.